Nutrition Knowledge Scale (NKS): Development, Factor Structure, and Validation for Healthy Adults - ÖNGÜN YILMAZ, Hande; AYDIN HAKLI, Duygu; TOĞUÇ, Hakan; ÇOBANOĞLU, Zeynep; ÖNEL SAYAR, Canel; ERKUL, Cahit; MURAT GÜNAL, Ahmet (Progress in Nutrition, 2021)
Objective: Valid and reliable scales are required to determine and evaluate nutritional knowledge. This research aims to develop the nutrition knowledge scale for adults and to examine the factor structure, validity, and reliability. Methods: Initially, the Nutrition Knowledge Scale (NKS) was constituted, paying attention to content and construct validity. The content validity index (CVI) was found as 0.884. Five hundred eighty-five (371 females, 214 males) volunteers consisting of healthy adults completed the general information form and NKS. For test-retest reliability, 164 (28.03%) participants completed the NKS again within four weeks following the first conduct. Results: As a result of Explanatory Factor Analysis (EFA), NKS items were collected under one factor. According to the results of the Confirmatory Factor Analysis (CFA), all fit indices were found at an acceptable level. Cronbach’s alpha value calculated for reliability analysis of NKS is 0.851. The intraclass correlation coefficient (ICC) calculated for test-retest reliability is 0.863. Conclusion: This research indicates that NCS is an acceptable, valid, and reliable scale that covers all aspects of nutritional knowledge and can be used in future research for determining and evaluating the nutritional knowledge level of adults.